2014
DOI: 10.1177/0161734614524179
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Ultrasound Imaging for Monitoring In Situ High-Intensity Focused Ultrasound Exposure

Abstract: Quantitative ultrasound (QUS) imaging is hypothesized to map temperature elevations induced in tissue with high spatial and temporal resolution. To test this hypothesis, QUS techniques were examined to monitor high-intensity focused ultrasound (HIFU) exposure of tissue. In situ experiments were conducted on mammary adenocarcinoma tumors grown in rats and lesions were formed using a HIFU system. A thermocouple was inserted into the tumor to provide estimates of temperature at one location. Backscattered time-do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 41 publications
(93 reference statements)
1
23
0
Order By: Relevance
“…In the hyperthermia range below 50° C, attenuation changes up to 10–20%, BSC changes of an order of magnitude, and 30% changes in ESD and EAC were all reported as more sensitive than thermally-induced changes in speed of sound. In their most recent work (144), the relationship between ESD, EAC, and temperature was extended up to 80° C in experiments with in situ rat tumors. Good linear regression with temperature was observed in three out of four rats.…”
Section: Specific Strategies For Ultrasound Thermometry and Ablatimentioning
confidence: 99%
“…In the hyperthermia range below 50° C, attenuation changes up to 10–20%, BSC changes of an order of magnitude, and 30% changes in ESD and EAC were all reported as more sensitive than thermally-induced changes in speed of sound. In their most recent work (144), the relationship between ESD, EAC, and temperature was extended up to 80° C in experiments with in situ rat tumors. Good linear regression with temperature was observed in three out of four rats.…”
Section: Specific Strategies For Ultrasound Thermometry and Ablatimentioning
confidence: 99%
“…[15][16][17] Ultrasound tissue characterization techniques have been developed to overcome the limitations of B-scan imaging, and enable quantitative assessments of tissue properties of both normal and diseased tissues. 17 Quantitative ultrasound techniques have employed various parameters to characterize tissues, including the speed of sound, 18,19 absorption and attenuation coefficients, 18,20 nonlinearity parameter, 21 angular scattering, 22 backscatter coefficient, 23-25 integrated backscatter coefficient (IBC), 18,25,26 effective scatterer diameter, 27 midband fit, 16,28,29 spectral intercept, 28 and spectral slope. 16,28,29 These parameters can provide estimates of the density, size, and spatial organization of acoustic scatterers in tissue.…”
Section: Introductionmentioning
confidence: 99%
“…17 As examples, quantitative ultrasound techniques have been used to characterize various tumors, 19,30 evaluate cardiac abnormalities, 31 monitor cell death, 29,32 characterize human dermis and subcutaneous fat, 33 and assess therapeutic responses in diseased tissues. 27,34,35 Several recent studies have shown that quantitative ultrasound can provide an important tool for the field of tissue engineering. 36 The midband fit and spectral slope parameters were employed to evaluate the mineral content of collagen constructs with hydroxyapatite 16 and monitor osteoblastic differentiation in engineered tissues in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…35 A second group is comprised of parameters that can be extracted from the power spectrum of the backscattered RF signals. These frequency-dependent parameters include the midband fit, 36,37 spectral intercept, 37 spectral slope, 33,37 backscatter coefficient, 33,38 effective scatterer diameter, 38 and integrated backscatter coefficient (IBC). 34,39,40 The absorption and attenuation coefficients of materials can be measured by analyzing either the amplitude or the frequency spectrum of the backscattered RF signals.…”
Section: Quantitative Ultrasoundmentioning
confidence: 99%
“…31,41-43 In native tissues, quantitative ultrasound techniques have been used to characterize tumors, 43 monitor cell death, 37,44 assess cardiac abnormalities, 45 characterize ultrasound contrast agents, 46 and evaluate therapeutic responses of diseased tissues after treatments with high intensity focused ultrasound or chemotherapeutic agents. 38,47,48 Furthermore, employing high-frequency ultrasound increases the backscatter coefficient of sub-resolution scatterers in tissues, such as cells and collagen fibers. High-frequency ultrasound has been employed to investigate the backscatter coefficient of blood during clotting, 39 to assess backscatter properties of cells and isolated nuclei, 34,49 to characterize human dermis, 39,50 and to monitor cell death in vitro.…”
Section: Quantitative Ultrasoundmentioning
confidence: 99%